Patterns of Injuries in Drowning Patients - Do These Patients Need a Trauma Team? - Hunn, Eric; Helmer, Stephen; Reyes, Jared; Haan, James (Kansas Journal of Medicine, 2020)
Introduction. Drowning is a major public health hazard worldwide, but associated traumatic injuries are rare. This study examined injuries and interventions performed on this population to assess the need for the trauma team activation.Methods. A 12-year retrospective review was conducted on all fatal and non-fatal drowning patients who underwent a trauma work-up. Data collection included demographics, injury characteristics, interventions, and outcomes.Results. Forty-three patients met inclusion criteria. Median patient age was six years (interquartile range 2 - 20) with 27.9% of patients under the age of 2 years. Most patients were white (62.8%) and male (69.8%), with median GCS score of 3 (60.5% had initial GCS = 3 with 25.6% with GCS = 15). Only two patients suffered traumatic injuries. Only two patients required operations, neither of which suffered traumatic injury. Eleven patients suffered anoxic brain injury (25.6%). Overall mortality was 48.8% (n = 21).Conclusion. Patients who present with drowning and no traumatic mechanism have a very low rate of traumatic injuries. Work-up and treatment would be appropriate for emergency physicians without the need for a trauma activation.